High Efficiency of Dye-Sensitized Solar Cells Based on Ruthenium and Metal-Free Dyes - Che-Lung Lee; Wen-Hsi Lee; Cheng-Hsien Yang (International Journal of Photoenergy)
The influence of using different concentrations of triazoloisoquinoline based small molecule as coadsorbent to modify the monolayer of a TiO2 semiconductor on the performance of a dye-sensitized solar cell is studied. The co-adsorbent significantly enhances the open-circuit photovoltage (), the short circuit photocurrent density () the solar energy conversion efficiency (). The co-adsorbent 4L is applied successfully to prepare an insulating molecular layer with N719 and achieve high energy conversion efficiency as high as 8.83% at 100 mW cm−2 and AM 1.5 at 1 to 0.25 (N719 : co-adsorbent) molar ratio. The resulting efficiency is about 6% higher than that of a nonadditive device. The result shows that the organic small molecule 4L (2-cyano-3-(5-(4-(3-oxo-[1,2,4]triazolo[3,4-a]isoquinoline-2(3H)-yl)phenyl)thiophene-2-yl)acrylic acid) is the promising candidates for improvement of the performance of dye-sensitized solar cell.